Engineering Fibrin Hydrogels to Promote the Wound Healing Potential of Mesenchymal Stem Cell Spheroids - Murphy, Kaitlin C. (Acta Biomater, 2017)
Mesenchymal stem cells (MSCs) secrete endogenous factors such as vascular endothelial growth factor (VEGF) and prostaglandin E2 (PGE(2)) that promote angiogenesis, modulate the inflammatory microenvironment, and stimulate wound repair, and MSC spheroids secrete more trophic factors than dissociated, individual MSCs. Compared to injection of cells alone, transplantation of MSCs in a biomaterial can enhance their wound healing potential by localizing cells at the defect site and upregulating trophic factor secretion. To capitalize on the therapeutic potential of spheroids, we engineered a fibrin gel delivery vehicle to simultaneously enhance the proangiogenic and anti-inflammatory potential of entrapped human MSC spheroids. We used multifactorial statistical analysis to determine the interaction between four input variables derived from fibrin gel synthesis on four output variables (gel stiffness, degradation rate, and secretion of VEGF and PGE(2)). Manipulation of the four input variables tuned fibrin gel biophysical properties to promote the simultaneous secretion of VEGF and PGE(2) by entrapped MSC spheroids while maintaining overall gel integrity. MSC spheroids in stiffer gels secreted the most VEGF, while PGE(2) secretion was highest in more compliant gels. Simultaneous VEGF and PGE(2) secretion was greatest using hydrogels with intermediate mechanical properties, as small increases in stiffness increased VEGF secretion while maintaining PGE(2) secretion by entrapped spheroids. The fibrin gel formulation predicted to simultaneously increase VEGF and PGE(2) secretion stimulated endothelial cell proliferation, enhanced macrophage polarization, and promoted angiogenesis when used to treat a wounded three-dimensional human skin equivalent. These data demonstrate that a statistical approach is an effective strategy to formulate fibrin gel formulations that enhance the wound healing potential of human MSCs.